The Value of Political Geography: Evidence from the Redistricting of Firms - Joaquín Artés; Brian Kelleher Richter; Jeffrey F. Timmons (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2019)
We demonstrate that political geography has value to firms. We do so by exploiting shocks to political maps that occur around redistricting cycles in the United States. These keep some firms in Congressional districts that are largely unchanged at one extreme and reassign other firms to entirely new sets of constituents at the other extreme. Our main finding is that firms suffer from being reassigned into districts that are competitive across parties relative to safer districts. The effects are not trivial in magnitude. Moreover, they do not depend on whether firm retain the same politician or actively make campaign contributions.
Keywords: D72; 330; Political Geography; Redistricting; Capture Theory; Representation